New trends in sustainable supply chains: insights from recent studies - Mukanov, Tynchtyk; Umetaliev, Akylbek; Mambetkulova, Asel; Kaiyrbekov, Almaz; Goncharova, Irina; Veres, Péter; Tamás, Péter; Kannazarova , Zulfiya (Advanced Logistic Systems - Theory and Practice, 2024)
Research on the Sustainable Supply Chain is a significant focus within the academic community, highlighting the importance of smart logistics, smart transportation, and digital technologies. This paper reviews current research trends from 2014 to 2023 by analyzing publications from the Web of Science database. The bibliometric analysis covers publication counts, document types, top-cited papers, leading journals, main funding sponsors, and distribution by subject categories, countries, and institutions. Additionally, co-authorship and keyword co-occurrence were examined to identify key knowledge components and research clusters. The analysis underscores the need for expanded international research and continuous integration of Sustainable Supply Chain concepts for future development. The goal of the document is to provide a comprehensive review of research and industrial trends and key insights in the fields of smart logistics, smart transportation, and digital technologies in recent years.